A ESTIMAÃ‡ÃƒO DE COMPONENTES DE VARIÃ‚NCIA NOS EXPERIMENTOS EM LÃTICE QUADRADO - Pimentel-Gomes, F. (REVISTA DE AGRICULTURA, 2020)
A ESTIMAÃ‡ÃƒO DE COMPONENTES DE VARIÃ‚NCIA NOS EXPERIMENTOS EM LÃTICE QUADRADO